(untitled) (Circe de clásicos y modernos, 2018)
In chapter 14 of book 5 of the Stromateis, Clement presents profusion of quotations of Greek authors in order to prove Greek plagiarism from Hebrew philosophy. Among several writers quoted, the Alexandrian transmits many verses that he attributes to the poet Orpheus. In this article, we will analyze the orphic poems he utilizes and the interpretations that he assigns to them, in order to examine his diverse uses of orphic writings and of Greek texts in general. We will attempt to elucidate the ways of appropriation and of reworking of orphic ideas in a Christian author in which specifically theological concerns converge with intentions of apologetic character.